The most recent record of †Palaeospheniscus bergi Moreno & Mercerat, 1891 (Aves, Spheniscidae) from the middle Miocene, northeastern Patagonia - Acosta Hospitaleche, Carolina Ileana Alicia (2012)
A penguin humerus constitutes the most recent record of the widely distributed genus Palaeospheniscus in the Atlantic Ocean. Penguins are unknown in late Miocene and Plicene beds in the region, whereas they have been reported from the occidental coasts of the continent. The gap in the record is occasioned mainly by the dearth of beds of this age. The present finding confirms that a high diversity still existed in the middle Miocene.